Membangun Frontend Website Pertanian Sebagai Media Edukasi Interaktif Menggunakan Framework Angular Js - Satria Agung Pratama JS; Abdul Haris (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2022)
Agriculture is one of the pillars of the life of the Indonesian nation. Indonesian agriculture became world famous with the title of the best spice producer in the world and became a Southeast Asian rice barn at that time. Time and history have changed along with the many changes that have occurred in various fields where rice farming has also become a developing field with agricultural techniques that have developed more advanced than conventional agriculture. However, unfortunately the current developments are not accompanied by an even distribution of education received by farmers from cities to remote rural areas who still use conventional processing techniques so that the productivity produced is far in comparison to farmers who use more modern farming techniques supported by broader knowledge. Based on the problems above, the creation of a website containing education in the form of videos and articles on agriculture, especially rice, is more modern so that farmers in remote areas are not left behind byfarmers in urban areas. The choice of website as an educational tool is because it is more effective and efficient in reaching very remote areas. By looking at smartphone usage data which continues to increase and there is no need to install an application to access this website, this is the main reason for choosing a website as the main means of conveying information. It is hoped that with this writing or research, the gap in knowledge of rice cultivation in urban and rural areas will be narrowed so that the productivity of rice farming will increase so that farmers will prosper.